Proceedings of the 2020 ACM Designing Interactive Systems Conference 2020
DOI: 10.1145/3357236.3395441
|View full text |Cite
|
Sign up to set email alerts
|

Participatory Memory Making

Abstract: As technologies become pervasive, so does participation in memory making. But in contested environments and discourses, certain voices are rarely included in public memory. In this paper, we explore how everyday postcolonial memories of Namibian youth engaged the wider public into a dialogue revisiting narrative of the past in order to explore alternative futures. Voices of the youth were amplified through an experimental participatory public exhibition leveraging interactive technologies. The exhibition resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The social worker reported that, during the interruptions happening between the actual deployment of the prototyping interventions, the elderly people were repeatedly asking when the new trip would happen and with which driver, whether s/he was the same as the previous trip or imagining how s/he would be like and drive. Moreover, remote passengers actively requested far away trip destinations to other continents [42] since Co-Drive could represent for them an accessible alternative to get an experience of travelling, though different from a real travel, to places that they couldn't reach due to old age related health and mobility issues.…”
Section: Fighting Isolation and Solitudementioning
confidence: 99%
“…The social worker reported that, during the interruptions happening between the actual deployment of the prototyping interventions, the elderly people were repeatedly asking when the new trip would happen and with which driver, whether s/he was the same as the previous trip or imagining how s/he would be like and drive. Moreover, remote passengers actively requested far away trip destinations to other continents [42] since Co-Drive could represent for them an accessible alternative to get an experience of travelling, though different from a real travel, to places that they couldn't reach due to old age related health and mobility issues.…”
Section: Fighting Isolation and Solitudementioning
confidence: 99%